Inward investment will fall in the UK, post Brexit - David Bailey; Nigel Driffield; Michail Karoglou (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
The UK has been a bridge between the US and Europe, and more recently between Asia and Europe. The more trade barriers that exist between the UK and Europe, the less attractive the UK will become. In many sectors and in many regions inward investment is likely to decline.
Keywords: 330